2022
DOI: 10.1093/ehjcvp/pvac034
|View full text |Cite
|
Sign up to set email alerts
|

Associations between medical therapy after surgical aortic valve replacement for aortic stenosis and long-term mortality: a report from the SWEDEHEART registry

Abstract: Aims The association between use of statins, renin-angiotensin system (RAS) inhibitors and/or β-blockers and long-term mortality in patients with aortic stenosis who underwent surgical aortic valve replacement (SAVR) is unknown. Methods and results All patients with aortic stenosis who underwent isolated first time SAVR in Sweden from 2006 to 2017 and survived six months after discharge were included. Individual patient data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Magne et al showed that RAS inhibitors were associated with improved clinical outcomes for patients after SAVR ( 32 ). The results from a recent large real-world population-based study supported the use of RAS inhibitors for patients after SAVR due to AS ( 33 ). Three previous systematic reviews and meta-analysis ( 34 36 ) explored the impact of RAS inhibitors on patients after AVR (TAVR and/or SAVR), and demonstrated that RAS inhibitors could lower the all-cause mortality rate for patients after AVR.…”
Section: Discussionmentioning
confidence: 79%
“…Magne et al showed that RAS inhibitors were associated with improved clinical outcomes for patients after SAVR ( 32 ). The results from a recent large real-world population-based study supported the use of RAS inhibitors for patients after SAVR due to AS ( 33 ). Three previous systematic reviews and meta-analysis ( 34 36 ) explored the impact of RAS inhibitors on patients after AVR (TAVR and/or SAVR), and demonstrated that RAS inhibitors could lower the all-cause mortality rate for patients after AVR.…”
Section: Discussionmentioning
confidence: 79%
“…[10][11][12] RAS inhibitors have been shown to be associated with improved outcome after TAVI, 13 but there are no large longterm studies after SAVR, except a recent study where associations between different secondary prevention medications and mortality were investigated. 14 In that study, an association between RAS inhibition and lower all-cause mortality was observed. In the current study, partly based on the same patient cohort, we aimed to evaluate if there is an association between RAS inhibition and major adverse cardiovascular events (MACEs) after SAVR, if there are subgroups of SAVR patients with more noticeable associations for any of the endpoints and if potential associations with long-term outcomes differ between ACE inhibitors and ARBs.…”
Section: Introductionmentioning
confidence: 79%
“…Based on information from Refs. [ [1] , [2] , [3] , [4] , [5] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [32] , [33] , [34] , [35] , [36] , [37] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The elements of the figure were created using SERVIER MEDICAL ART (CC BY 4.0).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the use of statins in patients undergoing SAVR reduced the risk of all-cause mortality (HR = 0.67; 95 % CI: 0.60–0.74). The use of statins does not affect the risk of AS [ 24 ]. In a study including 11894 patients after SAVR, it was found that ongoing statin treatment led to a reduced risk of: all-cause mortality (HR adj = 0.70; 95 % CI: 0.64–0.76), cardiovascular mortality (HR adj = 0.86; 95 % CI: 0.77–0.97) and MACE (HR adj = 0.77; 95 % CI: 0.71–0.83).…”
Section: Lipoprotein (A)mentioning
confidence: 99%